Cultivating Empathy and Anti-Bullying Values through Character Education Programs at SD Negeri 2 Kepanjen Jombang - Yunarta, Arsika; Prasetiyo, Rahayu; Synthiawati, Novita Nur (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
The phenomenon of bullying in the world of education today is a serious challenge because it negatively impacts the development of students' personality, psychology, and emotional well-being. Acts of bullying can cause physical and mental suffering, cause stress, depression, mental health disorders, and can even lead to suicide. This condition requires serious attention from various parties, especially educators, to create a safe, inclusive, and empathetic learning environment. Community service activities at SD Negeri 2 Kepanjen, Jombang Regency, were carried out with the aim of fostering empathy and anti-bullying behavior through character education. The training methods used are participatory, including lectures, interactive discussions, and question and answer sessions. The results of the activity showed that participants comprehensively understood the basic concepts, forms, causes, and legal consequences of bullying, and were aware of their roles and responsibilities in prevention in schools. In addition, there is an increased understanding of the concept of empathy, the negative impact of bullying, and prevention strategies. Teachers are also encouraged to play an active role in instilling the value of caring and respecting each other in the learning environment. Overall, these activities contribute to the formation of a school culture that is characteristic, humanist, and free from bullying behavior.